2006
DOI: 10.1016/j.bbmt.2006.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Donor-Derived Hematologic Malignancies after Hematopoietic Stem Cell Transplantation

Abstract: Increasing the upper age limit for recipients of hematopoietic stem cell transplantation (HCT) naturally has also increased the age of the corresponding related donor population. Because aging is a risk factor for malignancies, the risk of transferring preexisting malignant or premalignant hemopoietic clones in the process of HCT might be expected to increase as well. Anecdotal clinical cases of malignancies derived from donor cells in patients undergoing HCT have been published since 1971. In this article, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 33 publications
3
77
0
1
Order By: Relevance
“…Until 2005, reports of DCL were exclusively in allogeneic bone marrow HC transplant recipients; however, there have now been at least 4 cases reported in PB HC transplant recipients. 7,12 The first report in an UCB transplant recipient was in 2005 30 and was quickly followed by 2 additional cases reports. 31,32 The predominance of DCL in allogeneic BM HCTs compared with both PB and UCB may simply be a result of the longer historical use of this cell source.…”
Section: Stem Cell Source For Development Of DCLmentioning
confidence: 99%
See 1 more Smart Citation
“…Until 2005, reports of DCL were exclusively in allogeneic bone marrow HC transplant recipients; however, there have now been at least 4 cases reported in PB HC transplant recipients. 7,12 The first report in an UCB transplant recipient was in 2005 30 and was quickly followed by 2 additional cases reports. 31,32 The predominance of DCL in allogeneic BM HCTs compared with both PB and UCB may simply be a result of the longer historical use of this cell source.…”
Section: Stem Cell Source For Development Of DCLmentioning
confidence: 99%
“…In addition to de novo leukemia, there are cases documenting the occult transfer of malignant cells from donors during HCT. 7 Notably, transfer of malignant cells can also occur with solid-organ transplantation. [8][9][10] Defining the true incidence of DCL is difficult because of vagaries in its recognition and in reporting; therefore, the majority of evidence in the literature is anecdotal.…”
Section: Introductionmentioning
confidence: 99%
“…Transfer of leukemia by an allotransplant is reported in several leukemias including three cases of CLL. 27,28 Sala-Torra et al 28 suggested two mechanisms of donor-derived leukemia in the recipient. The first is the transfer of preleukemia cells from donor to recipient, most likely the scenario in our patient UPN 7.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found that deletion or mutation of functional genes in these niche cells led to MPNs, myelodysplasia, or leukemia [12,[28][29][30][31][32]. These findings and accordingly raised concepts were proved by the clinical transplantation investigations, in which donor-derived hematologic malignancies after hematopoietic stem cell transplantation were diagnosed [33].…”
Section: Oncogenesis In Abnormal Nichesmentioning
confidence: 97%